Miskonsepsi Proses Berpikir Peserta Didik dengan Pendidik pada Topik Pertidaksamaan - Herdiana, Nanang (LPPM Universitas Bina Bangsa, 2022)
Misconceptions of students or a wrong understanding of a mathematical concept are often found during learning as above the problem. Therefore, misconceptions are one of the things that must be considered in the world of education. All efforts to improve the quality of education ultimately aim to improve the abilities of students. One of the abilities of students can be seen from the students' understanding of a concept. Misconception is a part of the conceptual framework that is wrong but is considered correct by the learner so that errors occur that appear repeatedly and consistently. Analysis of the thinking process of students on this topic of inequality is carried out in order to obtain a clear picture of the occurrence of misconceptions experienced by students. So that a clear picture of this misconception will be used as a way to prevent misconceptions. The investigation of misconceptions in this study begins with describing the learners' mistakes in the topic of inequality. Continue to trace what misconceptions the learners experienced. So that a clear picture of the misconceptions of students on the topic of inequality is obtained. Based on this description, the researcher will examine with the title